Urban strategies for mitigation or adaptation to climate change: what criteria for choice - (:unkn) unknown (My University, 2023)
Strategies to combat climate change may be based on mitigation of the phenomenon or on adaptation to its consequences. This paper aims to identify the driving factors of the choice between these two categories of strategies in the context of urban climate plans. The fight against climate change being characterized by a logic of free riding, the situation tilts the balance towards adaptation strategies in an urban context, to the detriment of mitigation. This hypothesis is tested here through a review of the existing literature on urban climate strategies. This study shows that, counterintuitively, mitigation prevails over adaptation in urban climate strategies up to now. This paper explores the explanations for this seemingly paradoxical situation. We argue that a big part of the explanation has to do with the institutional context of urban climate strategies, specifically the decision-making capacities of municipalities, or the fact that they take part in international networks promoting mitigation over adaptation. Other explanations rely on the cost/benefit impact of adopting mitigation or adaptation, like the collateral local/private benefits of urban climate strategies that are often bigger with mitigation than adaptation. Another finding is that there is no systematic planning making it compulsory to choose between mitigation and adaptation strategies, as they are in some instances complementary, providing co-benefits.
Keywords: Sosyal ve Beşeri Bilimler; Coğrafya; Sosyoloji; İktisat; Jeofizik Mühendisliği; Mühendislik ve Teknoloji; Social Sciences and Humanities; Geography; Sociology; Economics; Geophysical Engineering; Engineering and Technology; Temel Bilimler (SCI); Sosyal Bilimler (SOC); Yerbilimleri; Ekonomi ve İş; Sosyal Bilimler Genel; COĞRAFYA; JEOKİMYA VE JEOFİZİK; EKONOMİ; KENTSEL ÇALIŞMALAR; ÇEVRE ÇALIŞMALARI; Natural Sciences (SCI); Social Sciences (SOC); GEOSCIENCES; ECONOMICS & BUSINESS; SOCIAL SCIENCES, GENERAL; GEOGRAPHY; GEOCHEMISTRY & GEOPHYSICS; ECONOMICS; URBAN STUDIES; ENVIRONMENTAL STUDIES; Küresel ve Gezegensel Değişim; Fizik Bilimleri; Coğrafya, Planlama ve Geliştirme; Sosyal Bilimler ve Beşeri Bilimler; Kentsel çalışmalar; Ekonomi ve Ekonometri; Yönetim, İzleme, Politika ve Hukuk; Global and Planetary Change; Physical Sciences; Geography, Planning and Development; Social Sciences & Humanities; Urban Studies; Economics and Econometrics; Management, Monitoring, Policy and Law; adaptation; Climate change; co-benefits.; mitigation; urban strategies